Pengendalian Kualitas Batu Bata Dengan Metode Seven Tools - Hidayat, Nurul; J, Nur Fatihah Amalina; Zhafirah, Yumna; Afuiata, Denisius (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to examine Barri Red Bricks from Tarakan, Indonesia, using the seven tools approach to find out how the quality of red brick products is controlled. This study employs a quantitative method based on descriptive statistics. Using the stratified randong sampling approach, 210 samples were collected throughout the course of 5 manufacturing runs for this investigation. Checking sheets, flow diagrams, histograms, Pareto diagrams, control charts, spreader diagrams, and cause and effect diagrams were the seven tools used to examine the data. This study's findings included four distinct sorts of defects: cracks (20%), chips (19%), broken 2%, and not ripe (57%). Out of the four categories of machine factors, raw materials, personnel, and techniques, the human element has the most impact on faulty products. The distribution diagram shows that human error is a contributing cause to product defects, while the control chart shows that Bari Red Bricks has managed to keep the defect situation under control.